Dancing the Urban Heritage - Semeghini, Juliana Raposo (Revista Brasileira de Estudos da Presença, 2021)
This article proposes to broaden the discussion of the threatened identity of the Urban Heritage, perceived within a culture of body reification, from the viewpoint of ephemeral arts. The ongoing research, from which this article derives, is interested in investigating authors who question documental representations, who recover forgotten cultural spaces and who propose a review of historical memory. The analysis of works that trace the genealogy of this ethnographic turn in art history contributed to the understanding of an artistic practice based on the sensitive world, related to its surroundings, in addition to providing clues about the artist capable of summoning others to a new kind of public experience.